Circular causality model: the relationship between GCG, CSR, intellectual capital, financial risk, and Islamic financial performance - Azwirman, Azwirman; Novriadi, Novriadi (JAS (Jurnal Akuntansi Syariah), 2025)
Purpose – This study aims to investigate the effects of good corporate governance (GCG), corporate social responsibility (CSR), intellectual capital (IC), financial risk, and sharia financial performance using the circular causality model in Indonesian Islamic banking. Method – The research population consisted of Islamic commercial bank (ICB) published by Bank Indonesia from 2015 to 2020. Purposive sampling was applied to select 48 annual reports from various Islamic banks. These reports were analyzed through the circular causality framework by examining causal relationships between variables using simultaneous equations and the dynamic two-stage least squares (2SLS) method with EViews 9 software. Findings – The results indicate that GCG negatively impacts Islamic financial performance. Similarly, CSR negatively affects financial performance, whereas IC shows no significant effect. No bidirectional influence was found between GCG and IC. Likewise, GCG and CSR do not influence each other. Neither GCG nor financial risk showed mutual effects. CSR and IC were not significantly related, but CSR and financial risk negatively affected each other. There was no influence between IC and financial risk. Implications – This study offers theoretical contributions by applying the circular causation approach (TSR), providing updated methodologies and managerial insights, and supporting FSA in developing performance indices for Islamic finance based on performance size ratios.